Analysis of Strawberry Farmerâs Satisfaction for Utilization of âXâ Fungicide in Pandanrejo Village, Batu City - Prihatmojo, Baskoro Aji; Anindita, Ratya (Department of Social Economy, Faculty of Agriculture , University of Brawijaya, 2017)
The objective of this research are to understand some factors that are affecting strawberry farmers satisfaction in utilization of âXâ fungicide and the level of farmer satisfaction. The location of this research in Pandanrejo Village, Batu City with 50 respndents. The method which was used in this research are decriptive statistics, Logistic Regression, and Customer Satisfaction Index (CSI). Measuring factors that affect satisfaction used four dummy variables, such as education level, group refference, training experience, and information source. And then to measure the level of satisfaction used variable of product attributes such as variety of product size, composition, expire date, procedure, permite of distribution, product availability, benefit, product information, completeness, rate of extermination ,and price. The result of logistic regression that group reference and source information are affecting the satisfaction of strawberry farmer. The obtained result of Customer Satisfaction Index method got 73,43% which means that strawberry farmer are satisfied with fungicide âXâ.